2006
DOI: 10.1074/jbc.m604317200
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA Polymerase N (POLN) Is a Low Fidelity Enzyme Capable of Error-free Bypass of 5S-Thymine Glycol

Abstract: Human DNA polymerase N (POLN or pol ) is the most recently discovered nuclear DNA polymerase in the human genome. It is an A-family DNA polymerase related to Escherichia coli pol I, human POLQ, and Drosophila Mus308. We report the first purification of the recombinant enzyme and examination of its biochemical properties, as a step toward understanding the functions of POLN. Unusual for an A-family DNA polymerase, POLN is a low fidelity enzyme incorporating T opposite template G with a frequency of 0.45 and G o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
206
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(219 citation statements)
references
References 50 publications
9
206
0
2
Order By: Relevance
“…Additionally, cells undergoing continuous DTB while exposed to MNNG do not appear to incorporate BrdU, whereas cells undergoing continuous aphidicolin block while exposed to MNNG do appear to incorporate BrdU at a low level. Taken together these results indicate that DNA repair synthesis is occurring in aphidicolin blocked cells, perhaps by the BER pathway and nonreplicative polymerases uninhibited by aphidicolin [46,57,58].…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, cells undergoing continuous DTB while exposed to MNNG do not appear to incorporate BrdU, whereas cells undergoing continuous aphidicolin block while exposed to MNNG do appear to incorporate BrdU at a low level. Taken together these results indicate that DNA repair synthesis is occurring in aphidicolin blocked cells, perhaps by the BER pathway and nonreplicative polymerases uninhibited by aphidicolin [46,57,58].…”
Section: Discussionmentioning
confidence: 65%
“…Recent data have shown that RB69 gp43 is blocked by both cis stereoisomers of Tg, (5R, 6S) and (5S, 6R), whereas several DNA polymerases of the A family are blocked by (5R, 6S) Tg but are able to bypass the (5S, 6R) isomer (34). In the (5S, 6R) isomer, the configuration at the C5 position is such that the methyl group would protrude axially toward the adjacent 3Ј base.…”
Section: Discussionmentioning
confidence: 99%
“…Tg was originally identified in purified DNA after oxidation with ionizing radiation (29). The Tg lesion is a block to human replicative DNA polymerases, but the lesion is tolerated because several translesion DNA polymerases readily bypass the lesion, including DNA polymerase Z, k, n, b, and l (6,28,50,84), with a minimal increase in mutations. Additional oxidized thymine analogues include 5,6-dihydro-thymine (dHT) and 5-hydroxy-5,6-dihydrothymine (Th5) (Fig.…”
Section: Oxidative Base Damage Repaired By Bermentioning
confidence: 99%